Imágenes indígenas del bosque chaqueño: Animales y plantas en el universo visual wichí - Rodrigo Montani (Caravelle)
In the visual universe of the wichís, an ancient nation of hunter-gatherers in the Gran Chaco, animals and plants occupy an outstanding place. This article describes cultural history, figurative strategies, plastic features and the context of production, circulation and comsuption of the four main wichís’ visual forms – string figures, braided patterns, wood carvings and graphics – in order to be able to discuss some of the interpretations of their meanings. The analysis highlights that wichís not only maintain an intimate relation – economical and symbolical – and a thorough knowlege of the Chaco’s forest, but that their animal and plant-like «figures» serve in different ways to build and rebuild a way of thinking, creating relations with themselves, the others and the world.